Odpowiedź :
Odpowiedź:
f(x)=3x-k-31 3x-k-31=0 3x=k+31 x= 1/2 k +31/3
f(x)=-2x+2k-4 -2x=-2k+4 x= k -2
1/2 k+31/3 - (k-2)=2
1/2 k +31/3-k+2=2
31/3=k-1/3 k
31/3= 2/3 k
k= 31/3: 2/3=31/3*3/2=31/2
Szczegółowe wyjaśnienie:
spr.
f(x)= 3x-31/2-31=3x-31/2-62/2=3x-93/2
g(x)= -2x+2*31/2 -4=-2x +31-4=-2x+27
3x-93/2=0 3x=93/2 x= 93/6= 31/2= 15,5=m-ce zerowe f(x)
-2x+2*31/2-4=0 2x- 27 x=13,5= m-ce zerowe
Obliczam miejsca zerowe funkcji
[tex]f(x) = 3x - k-31[/tex]
[tex]3x - k-31=0[/tex]
[tex]3x= k+31\ \ \ |:3[/tex]
[tex]x=\frac{1}{3}k+\frac{31}{3}[/tex]
[tex]g(x) = -2x + 2k - 4[/tex]
[tex] -2x + 2k - 4=0[/tex]
[tex] -2x= - 2k +4\ \ \ \:(-2)[/tex]
[tex]x=k-2[/tex]
Miejsca zerowe mają różnić się o 2, więc
[tex]\frac{1}{3}k+\frac{31}{3}-(k-2)=2\ \ \ lub\ \ \ k-2-(\frac{1}{3}k+\frac{31}{3})=2[/tex]
[tex]\frac{1}{3}k+\frac{31}{3}-k+2=2\ \ \ \ \ \ \ \ \ \ \ \ \ \ k-2-\frac{1}{3}k-\frac{31}{3}=2[/tex]
[tex]\frac{1}{3}k-k=2-\frac{31}{3}-2\ \ \ \ \ \ \ \ \ \ \ \ \ \ k-\frac{1}{3}k=2+2+\frac{31}{3}[/tex]
[tex]-\frac{2}{3}k=-\frac{31}{3}\ \ \ |:(-\frac{2}{3})\ \ \ \ \ \ \ \ \ \ \ \frac{2}{3}k=\frac{43}{3}\ \ \ |:\frac{2}{3}[/tex]
[tex]k=15,5\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ k=21,5[/tex]